2016
DOI: 10.1098/rspb.2016.0007
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic and bathymetric determinants of brachiopod extinction and survival during the Late Ordovician mass extinction

Abstract: The Late Ordovician mass extinction (LOME) coincided with dramatic climate changes, but there are numerous ways in which these changes could have driven marine extinctions. We use a palaeobiogeographic database of rhynchonelliform brachiopods to examine the selectivity of Late Ordovician -Early Silurian genus extinctions and evaluate which extinction drivers are best supported by the data. The first (latest Katian) pulse of the LOME preferentially affected genera restricted to deeper waters or to relatively na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 64 publications
(98 reference statements)
11
53
0
1
Order By: Relevance
“…The species that most strongly declined, in terms of their individual contributions to community composition, were preferentially those adapted to the mesopelagic habitat. Brachiopod species reveal a similar selectivity (18). Extinction of the majority of the graptolite species making up these stressed communities did not occur, however, until the onset of the glacial interval (or even later), when diplograptines were replaced by the neograptine species that migrated into the paleotropics and diversified during the Hirnantian Age.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The species that most strongly declined, in terms of their individual contributions to community composition, were preferentially those adapted to the mesopelagic habitat. Brachiopod species reveal a similar selectivity (18). Extinction of the majority of the graptolite species making up these stressed communities did not occur, however, until the onset of the glacial interval (or even later), when diplograptines were replaced by the neograptine species that migrated into the paleotropics and diversified during the Hirnantian Age.…”
Section: Discussionmentioning
confidence: 85%
“…The loss of graptolite biodiversity in the LOME, accompanied by the wholesale extinction of the previously dominant Diplograptina (taxonomic use follows ref. 11) and their replacement by the previously marginal, high-latitude Neograptina (12)(13)(14)(15)(16), provides an opportunity to study the impact of climate change on a macroplanktonic invertebrate fauna over several million years during an interval of unusual species turnover (17,18). A focus on climate change over geological timescales as a driver of extinction dynamics leads us to ask whether there is evidence of ecological community changes in the interval leading up to mass extinction.…”
mentioning
confidence: 99%
“…The results of this phylogeny are then used to reconstruct biogeographical and ecological changes across the evolutionary history of basal strophomenoids to investigate survivorship trends across the extinction event, as well as to determine whether the phylogenetic evidence confirms the latitudinal selectivity proposed by previous taxonomic studies (Finnegan et al . ).…”
mentioning
confidence: 97%
“…; Finnegan et al . , ). However, despite the large loss of global biodiversity, the ecological impact of this extinction has been considered minimal, with most families surviving and ecosystems largely returning to similar ecological associations after the event (McGhee et al .…”
mentioning
confidence: 99%
“…Recently, Finnegan et al (2016) suggested that the end Ordovician mass extinction was strikingly selective with respect to bathymetric distribution.…”
Section: Was South China a Refuge?mentioning
confidence: 99%